Remote Continuous Health Monitoring System using Wearable Sensors Networks and IoT - Sundarmani, R.; Venusamy, Kanagaraj; Kannadhasan, S.; Makimaa, Y. P.; Vanitha, D. Veera; Reddy, Poli Lokeshwara (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The huge expanding of the more seasoned population, higher caliber of distant medical services and therapy is presently expected in the developing nations. This consideration is particularly vital for the nations with 75% of the older people experiencing ongoing illnesses. Additionally, long haul observing of patients is a test to numerous families in this period of family units. Wireless Sensor Network (WSN) is turning into a promising innovation for different genuine applications. The high level miniature electro-mechanical frameworks (MEMS) with the sensor innovation persistently screen the ailment of a patient that is known as Wireless Body Area Network (WBAN).It can commonly expand over the entire human body and the hubs are associated through a remote correspondence channel. The compound sensor nodes in WBAN are fit for testing, handling, and imparting at least one imperative signs, for example, pulse, oxygen immersion level, action etc. as well as the ecological factors such as humidity, temperature, light and location, etc. of a patient and information transferred to far away using cloud platform. Enhanced wearable devices and cloud access delivers solution to health care field. In this paper, alongside the indispensable boundaries, the fatigue level and ecological boundaries likewise estimated and are sent through fringe interface to a Microcontroller unit (MCU). MCU is answerable for adjusting and investigating the crude information to remove the oxygen immersion, pulse, and temperature data, and afterward diverting the indispensable boundaries into the LoRa and Bluetooth module. The remote Bluetooth and LoRa module communicates these indispensable boundaries to different terminals, for example, cell phones and laptops. Any IoT stage can be utilized to store and recover the information. In light of the qualities got, the sicknesses are analyzed by the specialists from a good ways and caution is shipped off the patient.The test results show that the framework is compelling and dependable for the assortment, transmission, and show of ECG information continuously for the motivation behind tele monitoring of patients with coronary illness